Teoria i praktyka zarządzania kosztami w służbie zdrowia - Baran, Wioletta; Urbanek, Piotr (Theory and Practice of Costs Management in Health Service, 2005)
The aim of this article is to indicate the possibility of practical use of costs management system in the health care institution. Apart from costs recording for the accountancy needs - already in stage of data registration - it is proposed to apply them in the decision making model. As the basis for presented solution was assumed the implementation of management accounting system based on financial accounting system which has already existed in the medical institution.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 23-35